Nonsurgical Periodontal Therapy Combined with Laser and Photodynamic Therapies for Periodontal Disease in Immunosuppressed Rats - Bottura, P. E.; Milanezi, J.; Femandes, L. A.; Caldas, H. C.; Abbud-Filho, M.; Garcia, V. G.; Baptista, M. A. S. F. (Elsevier B.V., 2011)
Background. Periodontal disease is often associated with systemic diseases and is characterized by destruction of the tissues supporting the teeth. Patients using immunosuppressive drugs such as tacrolimus are among those who suffer from tissue destruction. Objective. We sought to evaluate the effects of laser and photodynamic therapies (PDT; nonsurgical) as an adjunct to scaling and rootplaning (SRP) in the treatment of corona-induced periodontitis in rats immunosuppressed with tacrolimus (Prograf).Materials and Methods. The animals were divided into 5 groups. Each groups had 6 rats. Group I, the control group, received only saline solution throughout the study period of 42 days and did not receive periodontal treatment; group II received saline solution and SRP; group III received tacrolimus (1 mg/kg per day) and was treated with SRP; group IV animals were treated identically to group III and then administered laser treatment; and in group V, the animals were treated identically to group III and then administered PDT.Results. Statistical analysis indicated decreased bone loss with the progression of time (P = .035). There was no difference between the bone loss associated with the types of treatment administered to groups I, II, and III (P > .9) or groups IV and V (P > .6). The analysis also indicated that immunosuppression was not a bone loss-determining factor.Conclusion. Laser and PDT therapies were effective as an adjunctive treatment to SRP in reducing bone loss caused by experimental periodontitis induced in animals being treated systemically with tacrolimus.